Karakterisasi Dan Pengelompokan Morfologi Tiga Galur Kacang Panjang (Vigna unguiculata var. sesquipedalis.) Generasi F4 - Amara Nur Aini; Elea Nur Aziza; Agus Wartapa (JURNAL VIGOR, 2026)
Long beans (Vigna unguiculata var. sesquipedalis) require superior strain development to support increased productivity. This research aims to identify the morphological diversity of the F4 generation long bean strain and determine the potential strain for further selection. The study used the individual observation method without repetition to evaluate the phenotypic segregation in three strains F4 (G1 = Strain 1, G2 = Strain 2, and G3 = Strain 3) with the Parama and Pertiwi varieties as comparisons. A total of 19 morphological characters were observed in 231 individuals of long bean plants of the F4 generation. Each plant is treated as an individual selection, analyzed using Hierarchical Cluster Analysis (HCA) with the UPGMA method. The main distinguishing characters between clusters include the coloring of anthocyanin pods, the color of the old pods, the color and pattern of the seeds, the color of the seeds in the hilum circle, and the color of the flower petals. G2, G3 strains, and most of the G1 strains are recommended as further selection materials based on the suitability of the observed phenotype character. Meanwhile, G1.8, G1.9, G1.12, G1.52, G1.74 and G1.79. have the potential to be used as cross elders because they show differences in morphological characteristics that can support the formation of diversity in the segregan generation. Keywords: Morphological Diversity, Cluster Analysis, Dendrogram, F4 Generation, Advanced Selection